Monte Carlo modeling of polarized light propagation in biological tissues. - Gangnus, S. V.; Matcher, S. J.; Meglinski, I. V. (Springer Science Business Media, 2004)
The application of polarization-sensitive optical coherence tomography (PS-OCT) creates new possibilities for biomedical imaging. In this work, we present a numerical simulation of the signal from a PS-OCT interferometer. We explore the possibility to retrieve information concerning the optical birefringence properties of multiple layered tissues from the depth-resolved PS-OCT interferometric signal in the presence of strong elastic light scattering. Our simulation is based on a Monte Carlo algorithm for the propagation of polarized light in a birefringent multiple scattering medium. Confocal and time-gated detection are also included. To describe the polarization state of light, we use the Jones formalism, which reduces the calculation time compared with the full Stokes-Müller formalism. To analyse the polarization state of the partially polarized back-scattered light, we applied a standard method using the Stokes vector, which is derived from the Jones vector. In this work, we examined the Stokes vector variations with depth for different tissue types. The oscillations of the Stokes vector are clearly demonstrated in the case of a uniform birefringent medium. We also investigated a two-layered tissue with a different birefringence of each layer. The Stokes vector variation with depth is compared to the uniform case and used to assess the depth-sensitivity of PS-OCT. Our simulation results are also compared with published experimental results of other groups